ANALYSIS OF THE CORPUS CALLOSUM MYELOARCHITECTONICS OF MATURE PEOPLE - Boіagina, O.D.; Kostilenko, Yu.P.; Zharova, N.V. (World of Medicine and Biology, 2021)
Serial semi-thin sections of laminated preparations of the corpus callosum of mature people were studied. It was found out that there is a tunnel network of interstitial fissures between the blood exchange microvessels and myelinated nerve fibres, which closes around the cellular portions. This interstitial network is an intermediate compartment between the blood flowing through the microvessels and the cells in which the interfascicular oligodendrocytes are cellularly distributed. In the corpus callosum, the entire transport system is completely aimed at ensuring the structural and functional stability of only the myelin sheaths of nerve fibres due to the secretory activity of interfascicular oligodendrocytes.
Keywords: corpus callosum; myeloarchitectonics; commissural cords; interfascicular oligodendrocytes; fibrillar astrocytes